Root Cause Analysis of Leakage Tube Boiler: A Study Case - Sitompul, Lydia Kartika Basaria; Priadi, Dedi (Journal of Materials Exploration and Findings, 2024)
Oil and gas industry can have catastrophic implications for human life, the environment, and the economy. This paper investigated failure analysis using root cause analysis especially for boiler tube leakage of Heat Exchanger. Identify the issue using microscopic examination and energy dispersive x-ray analysis were conducted on the tube inside and outside surface to determine root cause of the failure. The formation of a protective film in the aluminum-brass tube during the starting stage is very important for ensuring adequate film protection throughout the service life of the heat exchanger. During this stage, exposure to unpolluted water is essential. The dezincification corrosion suggested the disruption of the formation of the protective films by the cooling water medium on the inner tube, The entrapped leaked fluid from the inner tube at the interface between the inner tube and outer tube resulted in secondary damage due to galvanic corrosion at conducive area.